Enzyme-catalyzed preparation of chenodeoxycholic esters by an immobilized heterologous Rhizopus oryzae lipase - Quintana, Paula Gabriela; Canet, Albert; Marciello, Marzia; Valero, Francisco; Palomo, José M.; Baldessari, Alicia (Journal of Molecular Catalysis B: Enzymatic)
A lipase-catalyzed preparation of ethyl and stearyl esters of chenodeoxycholic acid is described. Stearyl chenodeoxycholate is a new product and both bile acid esters were prepared through an enzymatic approach for the first time. The heterologous Rhizopus oryzae lipase, immobilized on two different supports proved to be an efficient catalyst, even more active than Candida antarctica lipase, in the esterification reaction using a complex substrate such as a bile acid. The immobilization of the enzyme on Octadecyl Sepabeads at pH 7 and 25 °C was the best choice to catalyze the esterification reaction. The influence of various reaction parameters, such as nature of the alcohol, alcohol:substrate ratio, enzyme:substrate ratio, solvent and temperature, was evaluated. Using the response surface methodology and a central composite rotatable design, the conversion of stearyl chenodeoxycholate was optimized by means of the study of the effect of enzyme:substrate ratio and alcohol:substrate ratio. The value 20 for ratios (E/S) and (A/S) was predicted as the optimal value to reach the maximum conversion. However, including economic aspects these ratios can be reduced up to 15. The well-known advantages of biocatalysis and the activity shown by the immobilized heterologous lipase make the reported procedure a convenient way to prepare chenodeoxycholic esters. Fil: Quintana, Paula Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Canet, Albert. Universitat Autònoma de Barcelona; España Fil: Marciello, Marzia. Consejo Superior de Investigaciones Científicas. Instituto de Catalisis y Petroleoquímica; España Fil: Valero, Francisco. Universitat Autònoma de Barcelona; España Fil: Palomo, José M. Consejo Superior de Investigaciones ...